Crop residues for mulch and feed in crop livestock systems: Impact on maize grain yield and soil properties in the West African humid forest and Savanna zones - Larbi, Asamoah; Smith, Jimmy W.; Adekunle, I.O.; Agyare, Wilson Agyei; Gbaraneh, L.D.; Tanko, R.J.; Akinlade, J.; Omokaye, A.T.; Karbo, N.; Aboh, N. (Cambridge University Press, 2002)
A study was conducted in the humid-forest, forest-savanna, and Guinea savanna zones of West Africa from 1993 to 1999 to examine the effect of managing crop residues from cereal-legume cropping systems for mulch and fodder for sheeIncreasing the proportion of total crop residues produced from a unit area of land and used as mulch increased maize grain yield, soil organic carbon, nitrogen and available phosphorus. The extra increases obtained when more than half the crop residues were applied as mulch were relatively small, however, suggesting that 25-50% of the crop residues could be removed as feed without any detrimental effect. When any crop residues rejected by sheep were mixed with livestock urine and faeces and returned to the respective fields from where the crop residues had been removed, subsequent grain yield and soil organic carbon, nitrogen, and available phosphorus increased. The study demonstrated the possibility of managing crop residues for increased productivity in smallholder mixed croplivestock systems.